AN INTRODUCTORY STUDY OF FATAWA NAZIRIYYAH OF HAZRAT SYED NAZIR HUSSAIN DEHLAVI: AN ANALYSES - Hussan Farosh; Dr. Abzahir Khan; Dr. Muhammad Adil (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Hazrat Syed Nazir Hussain Dehlavi (1220-1320 AH/ 1805-1902 AD) was prominent Scholar of Ahli Hadith school of thought. His services are not just recognized in the region of subcontinent but all over the Muslim world. He compiled a lot of books in his life. He was a great Muhadith of that time as well as he was mufti and expert in Islamic jurisprudence. Among the services of him for Islam and Muslim Ummah, one of the fields is authorship and compilation. These works of Hazrat Syed Nazir Hussain Dehlavi was not just writing for the sake of writing as an academic hobby, but they were to find solutions to the necessary problems faced by the Muslim Ummah. His field of research was Qur'an, Hadith and Fiqha. The work under review "Fatawa Naziriya" is related to the art of jurisprudence and fatawa, which is a rare collection of jurisprudential issues and debates and is a unique and great achievement of this century. He compiled a valuable fatawa named "Fatawa Naziriya". In this fatawa he discussed different fields of Hadith and Fiqha, Fatawa Naziriya a well-known book of fatawa in Ahli Hadith School of thought. The writing style and analysis of the mention book has been discussed in said paper in detail. Hazrat Syed Nazir Hussain Mohadis Dehlavi (1220 AH-1320 AH / 1805-1902) was born in district Monger Bihar, India. His father's name is Syed Jawad Ali. He is Naqvi Hussaini Syed from Nanyal and Dadhiyal. He was brought up as a Shia in his childhood but later abandoned Shia due to mistrust. Hazrat Syed Muhammad Nazir Hussain Dehlavi read Arabic and Persian books from his father. After that, he went to the famous city of Patna in India with one of his peers, Bashir uddin to get further education. After that, he went to Sadiq Nagar, Bihar, where in the 1820 AD he met Syed Ahmad Shaheed Barelvi (1786-1831) who had a revolutionary disposition.[i] Fatawa Naziriya consists of three volumes, one thousand nine hundred and thirty-five (1935) pages and ninety-three thousand (947) fatwas. This collection of fatwa is the result of the efforts of Mulana Shamsul Haq Azimabadi, Mulana Abdur Rehman Mubarak Puri, disciples of Syed Nazir Hussain Dehlavi, while the task of revision was carried out by Mulana Shamsuddin Dehlavi. Fatawa Naziriya was published for the first time in 1915 AD/1333 AH from Dehli. In Fatawa Naziriyyah, there are twenty-four (427) fatwas of other muftis besides Mufti Nazir Hussain Dehlavi.